Students Economic Literacy between Real and Ideal - Maria Liana LĂCĂTUȘ; Camelia STĂICULESCU (Revista de Management Comparat International)
This paper presents vary perspectives on what could represent economic literacy, based on analysis of different tests of economic literacy used to identify economic knowledge and thinking skills of youngsters with special focus on students. The basic assumption is that although all tests of economic literacy are describing the minimum level of economic education needed for an optimal functioning and integration of a person in a contemporary society, for Romanian pre-university system, they are describing more an ideal for economic education than the existing reality. This assumption has been tested in a group of teachers of economics and business from 14 counties in Romania, including Bucharest, the capital city, that have provided information regarding economic knowledge and mentalities they identified at students.